The evolution of the European Union’s energy policy - Kusiak-Winter, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The main objective of this article is to present the evolution of the EU energy policy with particular reference to its legal conditions. It will present the directions of the changes in the EU legal regulations in recent decades in order. Central to this is an attempt to answer the question of whether the European Union’s ambitious goal to achieve climate neutrality by 2050, as proclaimed in the European Green Deal, should be viewed in terms of a continuation of the EU’s earlier energy policy, or perhaps more in terms of a kind of “revolution”, imposing the introduction of systemic changes in the energy sector of the Member States.
Keywords: EU’s energy policy; EU’s climate and energy policy; the European Green Deal